ANALISA DISPARITAS HARGA PENAWARAN TERHADAP HARGA PERKIRAAN SENDIRI PADA PEMILIHAN PENYEDIA JASA PEKERJAAN JALAN - Alfian Malik (Universitas Pasir Pengaraian, 2013)
Based on the records of the Ministry of Public Works, the number of contractors in Indonesia reaches 180 thousand companies. This number tripled compared with companies in Chinese State. The large number of companies lead to unfair competition in the construction business so would be contrary to the principles of procurement: efficient, effective, transparent, open, competitive, fair/non-discriminatory, and accountable. This study aims to analyze disparities of bid prices to Owner’s Estimate (OE), case studies of public procurementwithin Pemerintah Kabupaten Kampar, specifically on road and bridge work packages.